PKC, AKT and ERK1/2-Mediated Modulations of PARP1, NF-κB and PEA15 Activities Distinctly Regulate Regional Specific Astroglial Responses Following Status Epilepticus - Kim, Ji-Eun; Kang, Tae-Cheon (Frontiers in Molecular Neuroscience, 2019)
Status epilepticus (SE, a prolonged seizure activity) leads to reactive astrogliosis and astroglial apoptosis in the regional specific manners, independent of hemodynamics. Poly(ADP-ribose) polymerase-1 (PARP1) activity is relevant to these distinct astroglial responses. Since various regulatory signaling molecules beyond PARP1 activity may be involved in the distinct astroglial response to SE, it is noteworthy to explore the roles of protein kinases in PARP1-mediated reactive astrogliosis and astroglial apoptosis following SE, albeit at a lesser extent. In the present study, inhibitions of protein kinase C (PKC), AKT and extracellular signal-related kinases 1/2 (ERK1/2), but not calcium/calmodulin-dependent protein kinase II (CaMKII), attenuated CA1 reactive astrogliosis accompanied by reducing PARP1 activity following SE, respectively. However, inhibition of AKT and ERK1/2 deteriorated SE-induced dentate astroglial loss concomitant with the diminished PARP1 activity. Following SE, PKC- and AKT inhibitors diminished phosphoprotein enriched in astrocytes of 15 kDa (PEA15)-S104 and -S116 phosphorylations in CA1 astrocytes, but not in dentate astrocytes, respectively. Inhibitors of PKC, AKT and ERK1/2 also abrogated SE-induced nuclear factor-κB (NF-κB)-S311 and -S468 phosphorylations in CA1 astrocytes. In contrast, both AKT and ERK1/2 inhibitors enhanced NF-κB-S468 phosphorylation in dentate astrocytes. Furthermore, PARP1 inhibitor aggravated dentate astroglial loss following SE. AKT inhibition deteriorated dentate astroglial loss and led to CA1 astroglial apoptosis following SE, which were ameliorated by AKT activation. These findings suggest that activities of PARP1, PEA15 and NF-κB may be distinctly regulated by PKC, AKT and ERK1/2, which may be involved in regional specific astroglial responses following SE.